Highlighted Activities of ICCASA 2015 - Thanh Tung, Nguyen (EAI Endorsed Transactions on Context-aware Systems and Applications, 2015)
The Fourth International Conference on Context-Aware Systems and Applications (ICCASA 2015) [1] is jointly organized by EAI, Nguyen Tat Thanh University (NTTU), and Ba Ria-Vung Tau University (BRVTU) and endorsed by the European Alliance for Innovation (EAI), a leading community-based organization devoted to the advancement of innovation in the field of ICT. The event consists of a main track on context-aware systems and applications, and two special tracks on contextual recommendation systems and on computational aspects of context in natural language processing, respectively. Especially, there are three keynote speeches, which will be presented at ICCASA 2015 by prominent invited speakers.
Keywords: Context-awareness; Context-aware applications; Context-aware systems